2022
DOI: 10.1101/2022.10.02.510555
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amyloid beta 42 alters cardiac metabolism and impairs cardiac function in obesity

Abstract: There are epidemiological associations between obesity and type 2 diabetes, cardiovascular disease and Alzheimers disease. While some common aetiological mechanisms are known, the role of amyloid beta 42 (A[beta]42) in these diverse chronic diseases is obscure. Here we show that adipose tissue releases A[beta]42, which is increased from adipose tissue of obese mice and is associated with higher plasma A[beta]42. Increasing circulating A[beta]42 levels in non-obese mice had no effect on systemic glucose homeost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 76 publications
(110 reference statements)
0
0
0
Order By: Relevance
“…191,203 Interestingly, adipose tissue expresses and releases Aβ42 into circulation. 204 Some obesityrelated brain changes may be caused by dysregulation of adipokines such as leptin, which are secreted by adipose tissue and can influence plasticity, neurogenesis and inflammatory cytokine production in dementia-relevant brain regions such as the hippocampus. 205 Studies in AD models have suggested that leptin may have a therapeutic role in reducing Aβ and intracellular tau phosphorylation, thereby preventing synaptic dysfunction.…”
Section: Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…191,203 Interestingly, adipose tissue expresses and releases Aβ42 into circulation. 204 Some obesityrelated brain changes may be caused by dysregulation of adipokines such as leptin, which are secreted by adipose tissue and can influence plasticity, neurogenesis and inflammatory cytokine production in dementia-relevant brain regions such as the hippocampus. 205 Studies in AD models have suggested that leptin may have a therapeutic role in reducing Aβ and intracellular tau phosphorylation, thereby preventing synaptic dysfunction.…”
Section: Obesitymentioning
confidence: 99%
“…A high‐fat diet can also increase whole brain and hippocampal Aβ levels in Tg2576 and APP/PS1 transgenic mice 191,203 . Interestingly, adipose tissue expresses and releases Aβ42 into circulation 204 . Some obesity‐related brain changes may be caused by dysregulation of adipokines such as leptin, which are secreted by adipose tissue and can influence plasticity, neurogenesis and inflammatory cytokine production in dementia‐relevant brain regions such as the hippocampus 205 .…”
Section: Cardiometabolic Modifiable Risk Factorsmentioning
confidence: 99%